2020
DOI: 10.1016/j.tips.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Can Growth Factors Cure Parkinson’s Disease?

Abstract: Growth factors (GFs) hold considerable promise for disease modification in neurodegenerative disorders because they can protect and restore degenerating neurons and also enhance their functional activity. However, extensive efforts applied to utilize their therapeutic potential in humans have achieved limited success so far. Multiple clinical trials with GFs were performed in Parkinson's disease (PD) patients, in whom diagnostic symptoms of the disease are caused by advanced degeneration of nigrostriatal dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 93 publications
(126 reference statements)
0
32
0
Order By: Relevance
“…This model has some limitations, as embryonic rodent neurons are used and the growth factor deprivation or neurotoxin poisoning do not replicate the real pathological situation in Parkinson’s disease. Nevertheless, it is a widely used cellular model to test the efficacy of growth factors and small molecules before testing them in animal models of Parkinson’s disease [ 39 , 40 ]. It has been demonstrated that the preferred cellular substrate for FTO is not the m 6 A but its further modification N 6 2′-O-dimethyladenosine (m 6 Am), which is exclusively found adjacent to the 7-methylguanine (m7G) cap in mRNA [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has some limitations, as embryonic rodent neurons are used and the growth factor deprivation or neurotoxin poisoning do not replicate the real pathological situation in Parkinson’s disease. Nevertheless, it is a widely used cellular model to test the efficacy of growth factors and small molecules before testing them in animal models of Parkinson’s disease [ 39 , 40 ]. It has been demonstrated that the preferred cellular substrate for FTO is not the m 6 A but its further modification N 6 2′-O-dimethyladenosine (m 6 Am), which is exclusively found adjacent to the 7-methylguanine (m7G) cap in mRNA [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…GDNF has been shown to protect cultured embryonic dopamine neurons from growth factor deprivation induced apoptosis, as well as 6-OHDA-induced cell death in vitro and in vivo [ 38 , 40 ]. We, therefore, assessed the neuroprotective ability of different concentrations of FTO or ALKBH5 inhibitors in cultured growth factor deprived dopamine neurons.…”
Section: Resultsmentioning
confidence: 99%
“…GDNF has been shown to protect cultured embryonic dopamine neurons from growth factor deprivation induced, as well as 6-OHDA-induced cell death in vitro and in vivo 40,52 . We, therefore, assessed the neuroprotective ability of different concentrations of FTO or AlkBH5 inhibitors in cultured growth factor deprived dopamine neurons.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the potency of FTO inhibitors 2 and 3 in protecting and rescuing DA neurons in vitro is comparable to that of GDNF. Since GDNF, when directly injected into the midbrain, protects dopamine neurons also in animal models of PD, 52,53 it is logical to assume that FTO and AlkBH5 inhibitors can also be neuroprotective in vivo . The main limitation in the clinical use of GDNF and other neurotrophic proteins in the treatment of PD is their inability to pass through the BBB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation